1986
DOI: 10.1177/019459988609400506
|View full text |Cite
|
Sign up to set email alerts
|

ABR Results in Patients with Posterior Fossa Tumors and Normal Pure‐Tone Hearing

Abstract: Sixteen patients with confirmed mass lesions of the posterior fossa and normal hearing sensitivity for pure tones were studied. Patients' main symptoms, auditory brain-stem response (ABR), and lesion size were analyzed. All patients manifested neurologic and/or otoneurologic symptoms or complained of hearing difficulty disproportionate to their pure-tone findings. Interestingly, the patients in this select group were younger (mean = 34 years) than the typical patient with a posterior fossa tumor. ABR results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…Similar findings have been reported elsewhere [8,12,21], although totally opposite results have also been shown in which hearing was better in ears with extracanalicular AN rather than in intracanalicular lesions [3,14]. It has been suggested that medial tumors have more space available for expansion without a compressive effect leading to disequilibrium and gradual sensorineural hearing loss [14,15]. Nadol et al [16] suggested that simple compression of the nerve is not the cause of hearing loss, since a significant correlation could only be found between low-frequency hearing loss and tumor size.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar findings have been reported elsewhere [8,12,21], although totally opposite results have also been shown in which hearing was better in ears with extracanalicular AN rather than in intracanalicular lesions [3,14]. It has been suggested that medial tumors have more space available for expansion without a compressive effect leading to disequilibrium and gradual sensorineural hearing loss [14,15]. Nadol et al [16] suggested that simple compression of the nerve is not the cause of hearing loss, since a significant correlation could only be found between low-frequency hearing loss and tumor size.…”
Section: Discussionsupporting
confidence: 79%
“…Our study contrasts with the data of many recent studies that small intracanalicular tumors can be detected at a significantly lower rate by ABR than are larger, extracanalicular tumors [5,8,12,26]. These results rather indicate no significant differences in ABR findings between medially and laterally placed tumors, and are consistent with the results of Baguley et al [1], Dornhoffer et al [7], Musiek et al [15], and Pfaltz et al [18].…”
Section: Discussionsupporting
confidence: 77%
“…The sensitivity of ABR is proportional to the degree of hearing loss; therefore, individuals with SSNHL and vestibular schwannoma with mild or recovered hearing losses will be more likely to yield false-negative ABR results. 138 ABR evaluation may be offered for patients with SSNHL who do not wish to have MRI. There is a strong role for shared decision making and patient preference, as ABR has excellent sensitivity for medium-and large-sized tumors but may miss up to 42% of small or intracanalicular tumors.…”
Section: Supporting Textmentioning
confidence: 99%
“…The sensitivity of ABR is proportional to the degree of hearing loss; therefore, mild hearing losses or those that have recovered will be more likely to yield false-negative ABR results. 121 …”
Section: Auditory Brainstem Responsementioning
confidence: 99%